Metanarration of Islamophobia through Houellebecq's Soumission - Artanti, Yeni (Diksi, 2023)
The persistent conflict resulting from distinctions in our diverse world are sustained by suspicion and fear in public life, yet cultural products offer insights into societal issues, highlighting the significance of mutual respect and authentic freedom. This study examined Soumission (2015) by Houellebecq as its main data source to trace Islam and deconstruct intertextually its misconceptions in the novel. This study uses qualitative research steps in literary studies, namely by reading many times data sources, making notes, grouping data thematically, and analyzing it inductively. Results showed that in this novel, Islam is portrayed as a threatening, frightening, ambiguous religion that favors a patriarchal system that places women in a subordinate position. Based on an examination of the Quran and Hadith of Islam reveals that Islam is a peaceful religion that respects its adherents and provides them with clear instructions on what is right and wrong, prohibited and permitted. Critical readers have the right to question the portrayal of Islam in this work if it aims to ridicule religious individuals, particularly Muslims, necessitating a prudent response to counter the author's deception. Keywords: déconstruction, laí¯cité, metanarration, politique, satire